Risk assessing and privacy-preserving scheme for privacy leakage in APP - Xinyu WANG; Ben NIU; Fenghua LI; Kun HE (Tongxin xuebao)
The APP in smartphone contain various third-party services.However,the service providers illegally read the user’s private information.To address this problem,a privacy risk assessing scheme called PRAS was proposed.Firstly,a model was built to assess the risk of privacy leakage,by counting all the permissions acquired by each service providers and considering the non-linear impact of the permissions combination on privacy leakage.Then,by analyzing the balance between service quality and privacy-preserving,an optimal model was used to minimized the risk of private information leakage,and a permission management method was given to protect the privacy information among APP.The experiment results show that PRAS reduces the risk of privacy leakage by an average of 18.5%.